Haemophilus (actinobacillus) pleuropneumoniae infection in germfree piglets - Anderson, N.V.; King, C.A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Germfree piglets rapidly develop pneumonia after Haemophilus pleuropneumoniae is inoculated into the lung, providing a basis of comparison for future studies of pneumonia in SPF and conventionally reared piglets.
Keywords: Swine; Haemophilus pleuropneumoniae